No Need to Worry: Multiple Profiles of Philosophy of Education in, and in Relation to, the World of Education and the World of Philosophy - Misawa, Koichiro (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2016)
How concerned should we be about the state and status of philosophy of education? To this familiar worry, I maintain that there is no need to worry. In this essay, I try to secure this conclusion, not by shoring up the authority and identity of the discipline, but by asking the fundamental question: Who is and should be the audience for philosophers of education, and what does philosophy of education owe to whom? I argue that to be worthy of that name, philosophy of education ought to have educational significance and continue being philosophical, requiring the discipline to serve the interests of all the three audiences—other philosophers of education, non-philosophical educators, and non-educational philosophers. Through a close analysis of several important scholarly materials concerning the range, quality and relevance of philosophy of education, I urge that working out its disciplinary nature in a broad context of philosophy makes the discipline capable of fulfilling that promise.